2020
DOI: 10.7150/jca.46584
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a prior malignancy on the survival of patients with ovarian cancer: a population-based study

Abstract: Background: With the improvement in the prognostic outcomes of multiple malignancies, the population of cancer survivors is growing rapidly and is at higher risk of developing secondary ovarian cancer. However, the prevalence and clinical outcomes of prior cancer among newly diagnosed ovarian cancer patients remain unknown. Methods: Patients diagnosed with ovarian cancer between 2004 and 2015 were identified using the Surveillance, Epidemiology, and End Results database. Patients were divided into two groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…It is important to determine the clinical significance and survival outcome of previous malignancies, as these factors may influence clinical trial design, oncology practice, and treatment decisions. Hypothyroidism has recently been identified as a predisposing factor for the development of liver cancer 21 . However, the role of thyroid cancer in PLC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to determine the clinical significance and survival outcome of previous malignancies, as these factors may influence clinical trial design, oncology practice, and treatment decisions. Hypothyroidism has recently been identified as a predisposing factor for the development of liver cancer 21 . However, the role of thyroid cancer in PLC remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of a cancer history among individuals with a new cancer diagnosis may have important implications for the delivery of cancer treatment and survivorship care. Some reports, including those conducted using SEER data, have documented inferior overall survival among patients with certain cancer types, including breast, prostate, colorectal, uterine, thyroid, melanoma, and bladder, who have a prior cancer diagnosis compared to those without, even after accounting for demographic and tumor characteristics 2‐5 . For patients with these cancer types, prior cancer history may therefore influence decisions surrounding treatment for the newly diagnosed cancer.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the prevalence of the second or later cancer diagnoses may be consequential for several reasons. Some studies have suggested that, for certain cancer types, overall survival may be significantly lower for patients whose diagnosis is a second‐ or higher‐order primary, relative to those with a first primary cancer diagnosis 2‐5 . As a result, patients with a second or later primary cancer are often excluded from cancer clinical trials on the basis of their cancer history 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these concerns, for many common malignancies this commonplace exclusion criteria are poorly justi ed. Therefore, there have been some published literatures evaluating the effects of prior malignancy on patients with lung cancer, pancreatic adenocarcinoma, gastric cancer, colorectal cancer, laryngeal cancer, ovarian cancer, and prostate cancer [5][6][7][8][9][10][11][12][13][14][15] . According to 2020 FDA Cancer Clinical Trial Eligibility Criteria, patients with prior or concurrent malignancies of the same or different tumor type whose natural history or treatment does not have the potential to interfere with the safety or e cacy assessment of the investigational drug should generally be eligible for enrollment in clinical trials [16] .…”
Section: Introductionmentioning
confidence: 99%